STRATEGI PEMASARAN SELADA HIDROPONIK SECARA E-COMMERCE DAN KONVENSIONAL (SUATU KASUS PADA KEBUN RIYAN FARM) - Riyan Syarif Hidayatulloh; Suherna Suherna; Asih Mulyaningsih (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The Covid-19 pandemic is being felt in all sectors, including the agricultural sector and food UMKM. The agricultural sector is one of the priorities in dealing with the spread of Covid- 19 in Indonesia. The impact of the COVID-19 pandemic that was felt the most by farmers was the price of agricultural products which experienced a drastic decline due to the declining purchasing power of the people. This is not comparable to the effort and operational costs incurred by farmers when cultivating (Azamfirei, 2020). This research was conducted at the Riyan Farm Garden in Cipocok Jaya District, Serang City. This study aims to analyze the income of the hydroponic lettuce commodity as well as develop e-commerce and conventional marketing strategies that are appropriate to be implemented. The data used in this study are primary data and secondary data. Sampling was done by survey method, with 12 respondents. Collecting data using a questionnaire which is then analyzed using a SWOT analysis. The results of the calculation of the income analyst of hydroponic lettuce for the cost of production is Rp. 13,000/Kg. The profit obtained in terms of per kilogram on the sale of lettuce E-commerce is Rp. 7,000/Kg, while for conventional lettuce it is Rp. 2,603/Kg. The right strategy to be implemented based on the results of the SWOT analysis is to maintain existing potential markets and expand marketing reach. Optimizing cropping patterns according to SOPs to avoid production failures. Maintain product quality, manage product availability and increase product quantity. Innovate on products and add business partners to expand marketing.